Personality : An Introduction - Burger, Jerry M. (Philippines : Cengage Learning Asia, 2011)
This book was wrote to organize within one textbook the two approaches typically taken by instructors of undergraduate personality course. Many instructors focus on the great theories and theorist, including Freud, Jung, Rogers, and Skinner. Students in these classes gain insight into the structure of the mind and issues of human nature, as well as background for understanding psychological disorders and psychotherapy. However, these students are likely to be puzzled when they pick up a current journal of personality research only to find they recognize few, if any, of the topics. Other instructors emphasize personality research. Students learn about current studies on individual differences and personality processes. But they probably see little relationship between the abstract theories they may touch upon in class and the research topics that are the focus of the course. However, these two approaches to teaching the course do not represent separate disciplines that happen to share the word personality in their titles. Indeed, the structure of this book is designed to demonstrate that the classic theories stimulate research and that the research findings often shape the development and acceptance of the theories. Limiting a student's attention to either theory or research provides narrow view of the field.
Includes references, glossary and index.
Keywords: Personality -- Research